A GENERAL VIEW TO THE ECONOMIC LIFE OF ARTUQIDS - Hilal ARSLAN (Fırat University, 2019)
In the Upper Mesopotamian region, which was called al-Jazeera in history, the Artuqids who established three different principalities managed this geography in three centuries of prosperity. Artuqids, one of the principalities founded in Anatolia after the war of Malazgirt, have established an atmosphere of trust in the region with their constructive state policies. Both Muslims and non-Muslims, who were under their rule, managed the people with justice. Their economies, like every medieval state, were largely based on agriculture and trade. As a result of this, they tried to improve agriculture and trade with their policies. The presence on the Silk Road in the Middle Ages where the road trade was intensively contributed greatly to their economies. They made investments in order to benefit from the international trade flow and transformed their cities into commercial centers. With the markets and markets they have established, they have increased their economic power which has succeeded in attracting foreign merchants to their countries. In addition, they managed to keep the economic life alive by giving assurances to both domestic and foreign traders. They carried out effective policies for the continuity of agricultural life, which is another basis of their economies. The Artuqid beys, who ruled over fertile soils, evaluated this situation well. They have made the necessary assistance for their farmers to increase the production and even removed some taxes. In this period, the production of cereals, fruits and vegetables was made intensively in the cities of Artuqids. Water channels and cisterns have been built and used to meet the water needs of the farmers. The Artuqids have a strong economy with their productive Mesopotamia plain and the economic policies they follow.